2010
DOI: 10.1177/1947601910388271
|View full text |Cite
|
Sign up to set email alerts
|

A Role for OCT4 in Tumor Initiation of Drug-Resistant Prostate Cancer Cells

Abstract: Drug resistance remains a clinical challenge in cancer treatment due to poor understanding of underlying mechanisms. We have established several drug-resistant prostate cancer cell lines by long-term culture in medium containing chemotherapeutic drugs. These resistant lines displayed a significant increase in side population cells due to overexpression of drug efflux pumps including ABCG2/BCRP and MDR1/Pgp. To uncover potential mechanisms underlying drug resistance, we performed microarray analysis to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 41 publications
(49 reference statements)
4
79
0
Order By: Relevance
“…We found that TR4 may exert its action through Oct4-IL1Ra signaling. The role of Oct4 in drug-resistant PCa cells has been reported (18), and TR4 regulation of Oct4 has also been suggested (36). Our results showed TR4 modulation of Oct4 in PCa stem/progenitor cells and revealed its downstream molecule, IL1Ra.…”
Section: Cd133supporting
confidence: 68%
See 3 more Smart Citations
“…We found that TR4 may exert its action through Oct4-IL1Ra signaling. The role of Oct4 in drug-resistant PCa cells has been reported (18), and TR4 regulation of Oct4 has also been suggested (36). Our results showed TR4 modulation of Oct4 in PCa stem/progenitor cells and revealed its downstream molecule, IL1Ra.…”
Section: Cd133supporting
confidence: 68%
“…Linn et al (18) reported that drug-resistant PCa cells express high levels of Oct4, and knockdown of this molecule attenuated growth of the drug-resistant cells. Significant upregulation of Oct4 was also observed in cisplatin-resistant patients with oral squamous cell carcinomas (34).…”
Section: Tr4 Conferred Chemoresistance To Pca Stem/progenitor Cells Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Ponti and colleagues observed that a breast cancer cell line that developed into spheroids also had CD44+/CD24low/-phenotype and expressed the transcription factor OCT4 [91]. The expression of OCT4 has an essential role in carcinogenesis and offers a probable mechanism by which cancer cells obtain or sustain the therapy resistance phenotype [92,93]. Moreover, overexpression of this gene was related to metastasis and poor prognosis in various types of cancer, including colorectal, lung and gliomas [94][95][96][97][98][99].…”
Section: Effect Of Melatonin In Epithelial Mesenchymal Transition Marmentioning
confidence: 99%